Implementasi Musyarakah Mutanaqisah sebagai Alternatif Pembiayaan Murabahah di Perbankan Syariah Indonesia - M. Ridwan; Syahruddin - (TSAQAFAH, 2013)
Islamic banking and finance movement has now become mainstream with participation and competition from the leading,conventional banks. In Indonesia, majority of Islamic banking products is dominated by murâbahah. As the green-contract,  murâbahahalso has many shortcomings to be implemented in Islamic banking. It has potential deficiency for both customers and banks point of view. Alternatively, Musyaraka Mutanaqisa has several benefits that are not carried by murabaha. These advantages moreover can make Islamic banking productsto be competitive and attractive towards on-going dual banking system as being implemented in the most countries. This current modified contract can be an interesting alternative to murabahah especially for financing on real aset such as property. In other hand, there are some issues in musyaraka mutanaqisa  that should be revealed and educated to customers and banks to make this late product properly practiced. Some issues on the other hand, in this paper, the authors emphasized to classify into property indent financing, buying debts on debts, take over financing, taxations, annuity on profit distribution and the rest normative laws regarding with this hybrid contract.Overall,in ter m of compliancy of this product,it must be in line with sharia rules and regulations. The paper concludes that  Musyaraka Mutanaqisa can be practiced more widely as an alternative financing of murabahah which has been dominant applied to date by Islamic banking in Indonesia.